The Pandemic Origins of Child Baptism - Arduini, Francesco (Biblical archaeology review, 2021)
The article discusses the impact of Coronavirus Disease 2019 pandemic that limited religious practices and discusses history of other pandemics. It mentions that one ancient pandemic even helped to establish the Christian rite of baptism administered to little children and infants—a practice not attested in early Christian communities until the late second century. It also mentions that Christians likely managed to face and overcome the epidemic with greater success than pagans.